Biochemical changes in pear (Pyrus communis L. depending on different phases of the dormancy - Göndör, M.; Honty, K.; Pedryc, A.; Hajdrik, I.; Stefanovits-Bányai, É. (International Journal of Horticultural Science, 2004)
Pear cultivars of variable frost tolerance were tested as for frost injuries suffered as a consequence of artificial freezing temperatures during the endodormancy as well as the ecodormancy. Damages were registered according to a visually defined scale, then peroxidase and polyphenol-oxidase activity was checked in buds, spurs and limbs. According to our results, ’Packham’s Triumph’ was the most frost tolerant cultivar. Regarding enzyme activity of both enzymes, the performance of cultivars displaying different susceptibility was also different in spurs as well as in buds. Results referring to the endodormancy were especially instructive. During the ecodormancy, data obtained at the same time indicated the differences existing between the developmental stages of dormancy in the respective cultivars.